Balancing globalisation process through Development Agenda: sustainable global justice (Law and Safety, 2023)
The prevailing assumption was that the phenomenon of globalisation would yield equitable benefits for all nations. Nevertheless, it has become evident that the benefits of globalisation norms are predominantly enjoyed by affluent nations. Although the concept of globalisation was initially intended to enhance the agency of developing nations, it has instead resulted in the erosion of their autonomy to independently determine their course of action. The democratic process has been impacted by the loss of decision-making power experienced by emerging countries as a consequence of globalisation. The rules governing globalisation were inequitably formulated to provide preferential treatment to developed nations. Contrary to prevailing popular opinion, the impact of globalisation on both developing and affluent nations has exhibited disparities. The questioning of norms governing globalisation has emerged as a consequence of the phenomenon of globalisation. This process further exacerbated the existing division between the global north and global south, leading to a heightened level of separation between these two regions. International financial institutions based in Washington disregarded the objections raised by developing nations and formulated a strategy aimed at mitigating the disparity in wealth. The ideology of privatisation and the free market is commonly referred to as the Washington consensus. The concept of state non-intervention proved to be disappointing as it primarily served the interests of the international organisations involved, thereby failing to benefit other stakeholders. Hence, it is imperative to formulate a development strategy that encompasses principles of equity, justice, and long-term sustainability. The existing understanding of sustainable development and the approach to attaining justice through sustainability necessitate a reevaluation in order to accomplish similar objectives. The authors of this research endeavor to investigate the extent to which the current development agenda is sufficiently comprehensive to address the shortcomings of past attempts to reconcile globalisation with development. This study aims to examine the response of the global community to the phenomenon of globalisation through the implementation of the Development Agenda. This paper examines the influence of globalisation on the policy-making processes of developing nations. Finally, the authors proceed to analyse the concepts of justice, growth, and sustainability.
Keywords: Development Agenda; globalisation; global justice sustainability; sustainable development.